Cocaine-Induced Giant Bullous Emphysema - Steven Douedi; Vandan D. Upadhyaya; Ishan Patel; Usman Mazahir; Eric Costanzo; Mohammad A. Hossain (Case Reports in Medicine)
Background. Emphysematous bullae, defined as airspaces of greater than or equal to one centimeter in diameter, have a variety of etiologies such as tobacco use and alpha-1 antitrypsin being the most common. Emphysematous bullae have also been reported in patients using cocaine usually involving the lung periphery and sparing the central lung parenchyma. We present a case of a male with a history of cocaine abuse found to have a singular giant emphysematous bulla occupying >95% of the right hemithorax requiring video-assisted thoracic surgery (VATS) with a favorable outcome. Case Presentation. A 50-year-old male with a history of chronic cocaine abuse was found unresponsive in the field and given multiple doses of naloxone without any improvement in mental status. On presentation to the emergency department, chest X-ray as well as CT scan of the chest were performed which were suggestive of an extensive pneumothorax of the right lung requiring placement of a chest tube. The patient was subsequently intubated and underwent bronchoscopy with right chest VATS which found a giant bulla encasing the entire right pleural cavity. During the procedure, he underwent resection of the bullae and a partial right pleurodesis. After the procedure, patient’s respiratory status significantly improved, and he was discharged in a stable condition. Conclusion. Cocaine use is a rare but identifiable factor that can cause giant bullous emphysema (GBE) resulting in severe complications and even death. The purpose of this case presentation is to support early identification and treatment of GBE using bullectomy with VATS, improving outcomes and decreasing morbidity and mortality.